Crickets of the subfamily Itarinae Shiraki, 1930 (Orthoptera: Gryllidae) from China with description of a new species and distribution and critical notes on other species - He, Zhixin; Ma, Libin (Zootaxa, 2021)
The Itarinae includes two genera and 60 species world-wide. Ten species are recorded from China. All Chinese species were reviewed in this study. Females of the most species were described and illustrated. Keys based on characters of male and female for Chinese species were provided respectively. As well as, a new species and revised species distribution of Itara Walker, 1869 were reported. Two types of coloration (dark and light colors) of Parapentacentrus fuscus Gorochov, 1988 were discovered and taxonomic problem of the genus Parapentacentrus Shiraki, 1930 were discussed.